SURVEI UPAYA PENCEGAHAN DAN PENANGANAN PERILAKU BULLYING PADA SISWA DI UPT SPF SD INPRES MANGGALA - Andi Qosamah Qurratul Ain; Rahman, Abdul; Khaerunnisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Bullying behavior is one of the problems that arises in the school environment so that prevention and handling efforts are needed. This research aims to describe bullying behavior, find out the causes of bullying behavior, and describe teachers' efforts to prevent and handle bullying behavior among students at UPT SPF SD Inpres Manggala. The approach used in this research is descriptive quantitative with a survey type. The population in this study were students in grades IV, V, VI UPT SPF SD Inpres Manggala, with a total sample of 139 students selected using random sampling techniques. The instrument used was a questionnaire. The data analysis technique uses descriptive statistics (Percentage). The results of this study show that (1) there are four forms of bullying behavior: verbal, non-verbal, cyberbullying and relational bullying. Verbal bullying is the most dominant form with an average percentage of 47.57. (2) The most dominant cause of bullying behavior is lack of teacher supervision with a percentage of 37.41%. (3) The most dominant prevention efforts taken by teachers are active supervision in the school environment with a percentage of 79.67%, while the dominant handling efforts taken by teachers are mediation efforts with an average percentage of 69.78%. Based on the research results, it can be concluded that active supervision by teachers is a key factor in reducing bullying incidents in schools.